Change in the Ophthalmobiometric Parameters in Myopia and Hyperopia under the Influence of Cycloplegia - E. P. Tarutta; S. G. Harutyunyan; S. V. Milash; A. T. Khandzhyan; N. V. Khodzhabekyan (Oftalʹmologiâ, 2018)
Purpose: comparison of some ophthalmobiometric parameters in natural and cycloplegic conditions in myopia and hypermetropia.Material and methods: eyes biometric parameters were examined (the depth of the anterior chamber, the lens thickness and AL)before and after cycloplegia (1% Cyclopentolate hydrochloride — 2 times) in 244 eyes with myopic and hyperopic refraction in 122patients aged 5–32 years. Biometric parameters were examined on the Galilei G6 optical system analyzer (Ziemer Ophthalmic SystemsAG 6.0.6). The thickness of the choroid was measured with a spectral optical coherent tomograph (SD-OCT wavelength 800 nm) of Nidek RS-3000 Retina Scan Advance in 20 eyes of 10 patients aged 11 ± 1.3 years from the examined group before and 40 minutes after double injection of 1% Cyclopentolate hydrochloride. Results: the depth of anterior chamber and the axial, both in the narrow pupil and under the cycloplegia, are significantly higher in the myopic eyes than in the hyperopic eyes (p < 0.05 for ACD and p < 0.01 for AL), and the lens thickness is practically does not differ. In absolute terms, the position of irido-lens diaphragm, i.e. distance from the posterior surface of the cornea to the center of the lens in myopia group was significantly higher than with hyperopia respectively, of 5.62 ± 0.02 mm of 5.29 ± 0.01 mm (p < 0.01). However, the coefficient Lowе ((ACD + 1/2LT)/AL) in myopia was significantly lower (of 0.219 ± 0.001 and 0,238 ± 0,001, respectively) is due to the greater of the AL. After cycloplegia, in both myopic and hyperopic eyes, DAC increases: in myopia, on average, 0.12 mm, with hyperopia — by 0.14 mm, and accordingly the thickness of the lens decreases. The coefficient Lowe in both cases is increased by 0,04 mm. Interesting changes were observed in the length of AL: under conditions of cycloplegia, it decreased by 0.03 mm (30 microns) in eyes with myopia (p > 0.05) and by 40 microns (0.04 mm) with hyperopia (p < 0.01). Conclusion: In cyclopegic condidions, as compared to the existing accommodation, increasing the depth of the anterior chamber decreased the thickness of the lens center of the lens somewhat extended posteriorly and decreases the axial length. The revealed changes in the AL can be associated with a change in the position of the pigment epithelium layer due to changes in the thickness of the choroid under different accommodation conditions. The significant changes in the thickness of the choroid the influence of cycloplegia was not proved in this study.